Amendment and Repeal: Achieving Clarity of Drafting and other Needs at Issue - Albanesi, Enrico (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
When it comes to amendment and repeal, the challenge is to employ drafting techniques which simultaneously aim to provide the legislator with a precision-based mechanism for incorporating the existing legal system; and to deliver clarity for the user reading the Statute. The article will analyse techniques in the UK and Continental Europe (Italy will be taken as case study) in order to find combinations that deliver this goal. The analysis will be carried out against a holistic background: clarity and precision (plus effectiveness) will be prioritised in the light of a hierarchy of drafter’s goals.